2019
DOI: 10.1371/journal.pone.0217227
|View full text |Cite
|
Sign up to set email alerts
|

Measure and characterization of the forces exerted by growing multicellular spheroids using microdevice arrays

Abstract: Growing multicellular spheroids recapitulate many features of expanding microtumours, and therefore they are an attractive system for biomechanical studies. Here, we report an original approach to measure and characterize the forces exerted by proliferating multicellular spheroids. As force sensors, we used high aspect ratio PDMS pillars arranged as a ring that supports a growing breast tumour cell spheroid. After optical imaging and determination of the force application zones, we combined 3D reconstruction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…For WJ-MSCs, in the early stage of the cell spheroid growth, the surface pressure was high, resulting in high cell cohesion and aggregation. During the middle period to the late period of spheroid growth, the pressure was reduced, enabling rapid cell growth and amplification [42][43][44]. According to a previous study, increased pressure on the cell culture environment may promote the ossification of the MSCs [45].…”
Section: Discussionmentioning
confidence: 99%
“…For WJ-MSCs, in the early stage of the cell spheroid growth, the surface pressure was high, resulting in high cell cohesion and aggregation. During the middle period to the late period of spheroid growth, the pressure was reduced, enabling rapid cell growth and amplification [42][43][44]. According to a previous study, increased pressure on the cell culture environment may promote the ossification of the MSCs [45].…”
Section: Discussionmentioning
confidence: 99%
“…Turbulent airflow occurs above 40-80 Pa [23]; thus, nasal breathing may be 100 Pa and higher during intense physical exercise, such as vigorous play. Bernoulli forces of this magnitude represent 10 gm of compression pressure per sq cm and are many orders of magnitude larger than proliferative pressure exerted by mitotically growing tissues [24].…”
Section: Obligatory Nasal Breathing Is For Promoting Normal Facial Growth and Functionmentioning
confidence: 96%
“…4(h) ]. 189 In each of these studies, the induced prestress in the self-assembled tissues was found to be crucial for contractile functionality and for generating normal physiological responses. The balance in prestress magnitude also arises as an important parameter, where suboptimal stress can impede maturation, while excessive stresses triggers pathogenic fibrosis and hypertrophy.…”
Section: Measuring Forces At the Tissue Length Scalementioning
confidence: 99%